2012
DOI: 10.1002/dvdy.23861
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of synovial joints: Use of microarray analysis to identify factors that direct the development of the knee and elbow

Abstract: Background: Synovial joints develop from the interzone, a dense layer of mesenchymal progenitor cells that marks the site of the future joint. During the morphogenic events that follow, joints attain their distinct shape and organization. The molecular mechanisms controlling the initial specification of synovial joints has been studied, but the question of how individual joints attain the specific structure required for their unique functions remains largely unresolved. Here, we use microarray analysis to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 40 publications
(47 reference statements)
5
32
0
Order By: Relevance
“…These interesting findings raised the possibility that development of diverse limb joints may also involve differential responses to common cues such as muscle-driven movement. In a related and as interesting study, Pazin and collaborators carried out gene array-based molecular profiling to identify factors that direct the development of elbow and knee in mouse embryos (Pazin et al, 2012). They identified the period between E15 and E16 in which clear elbow- and knee-specific molecular identities could be uncovered.…”
Section: Regulators Of Interzone and Joint Formationmentioning
confidence: 99%
“…These interesting findings raised the possibility that development of diverse limb joints may also involve differential responses to common cues such as muscle-driven movement. In a related and as interesting study, Pazin and collaborators carried out gene array-based molecular profiling to identify factors that direct the development of elbow and knee in mouse embryos (Pazin et al, 2012). They identified the period between E15 and E16 in which clear elbow- and knee-specific molecular identities could be uncovered.…”
Section: Regulators Of Interzone and Joint Formationmentioning
confidence: 99%
“…Using Gdf5Cre mice to ablate floxed target genes, we and others showed that the behavior and function of interzone cells involve multiple mechanisms including Wnt/β-catenin signaling and cell surface/matrix macromolecule interactions (Koyama et al, 2008; Mundy et al, 2011). Recent studies have shown that joint formation also requires skeletal muscle function and contraction and signaling by β-catenin (Kahn et al, 2009; Pazin et al, 2012). The increasing research attention surrounding joint formation reflects the fact that many aspects of it remain stubbornly unclear and difficult to decipher, and that a much better understanding in this area could lead to the conception and creation of regenerative and repair tools for common and currently unsolved joint pathologies, including osteoarthritis (OA), severe joint injury, and congenital joint dysplasias (Onyekwelu et al, 2009; Sandell, 2012; Umlauf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Formation of joint-specific structures during embryogenesis is accompanied by tightly controlled topographical and temporal expression of specific sets of positional genes, including homeobox (HOX) transcription factors1. The highly conserved HOX transcription factors specify regional identities of cells and tissues throughout the body and regulate the correct formation of the body axes23.…”
mentioning
confidence: 99%